AN INVESTIGATION OF VIDEO COMMUNICATION OVER BANDWIDTH LIMITED PUBLIC SAFETY NETWORK - Ahmad, Raja Wasim; Shan, Rafi us; Rehman Khan, Atta ur; Bilal, Kashif; Shuja, Junaid; Sarwar, Shahzad; A.Altameem, Torki; A. Madani, Sajjad (Malaysian Journal of Computer Science, 2018)
Application performance of video-based services for public safety and security (PSS) systems is of high importance in order to protect citizens, organizations, and institutions against threats to their well-being. Video based services help PSS personnel to efficiently perform their rescue operations. Real-time video streaming of incident-based services over the PSS communication networks facilitates in realistic assessment of the situations and saves many precious lives. However, video communication over PSS networks, such as Terrestrial Trunked Radio (TETRA), is a big challenge due to the narrowband and the hostile environment. Thus, specialized codecs have been developed considering the constraints of the PSS networks. This paper presents performance comparisons of two video codecs, namely H.264/AVC and MPEG-4, over TEDS links. The significance of the results is evaluated using SPSS (t-test) to critically analyse the data. It is observed that video quality offered by H.264/AVC over TEDS links is better than the one offered by MPEG-4. Moreover, it is also noticed that TEDS bandwidth limitations substantially affect the quality of reconstructed video containing frequent changes of scenes. Based on the findings of our analyses, we propose a set of applications which are suitable for TEDS networks. The findings of this study would help the researchers to further explore the possibilities of video communication over TEDS links by optimizing the lower level network technologies.